2003
DOI: 10.1080/13577140310001607284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lung Metastases in Patients with Primary Extremity Sarcoma

Abstract: Twenty-three percent of patients in our study developed lung metastases. As the grade of the disease increased, metastases-free intervals are shortened. Although it has been reported that lung metastases in patients with extremity sarcomas may present as solitary or multiple nodules in earlier trials with radiographic screening methods, the current review of 400 patients found that a substantial number of patients may present radiological appearances other than nodular formations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
0
8
0
3
Order By: Relevance
“…In carcinomas, the metastatic progression requires trans-differentiation of epithelial to mesenchymal phenotype, a process releasing cells from adherent junctions and increasing their ability to migrate through extracellular matrix (2). This, however, is not the rule in sarcomas, which usually do not form metastases despite the mesenchymal character of sarcoma cells (4). Additional changes are necessary for the sarcoma metastasis and the knowledge of this regulatory level could contribute to our incomplete understanding of the metastatic propensity and development of effective therapeutics (5).…”
Section: Introductionmentioning
confidence: 99%
“…In carcinomas, the metastatic progression requires trans-differentiation of epithelial to mesenchymal phenotype, a process releasing cells from adherent junctions and increasing their ability to migrate through extracellular matrix (2). This, however, is not the rule in sarcomas, which usually do not form metastases despite the mesenchymal character of sarcoma cells (4). Additional changes are necessary for the sarcoma metastasis and the knowledge of this regulatory level could contribute to our incomplete understanding of the metastatic propensity and development of effective therapeutics (5).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study by Songur et al revealed malignant fibrous histiocytoma (22.2%), osteosarcoma (18.8%), and liposarcoma (15.5%) as the three commonest metastatic pulmonary lesions. [10] In another study amongst soft tissue sarcoma, leiomyosarcoma was the commonest (21%) type followed by malignant fibrous histiocytoma (18%), liposarcoma (12%) and synovial sarcoma (14%). [4] Previous studies have not demonstrated a relationship between histology of the metastatic lesion and outcome although some have shown a poor prognosis with liposarcoma (median survival 9.8 months).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the lung is the most common site for systemic sarcoma metastases because of the substantial vasculature that feeds into this organ, in addition to particular tropic factors (4). Other cancers that often metastasize to the lung include breast, colon, prostate, bladder, and various neuroblastomas (5). …”
Section: Introductionmentioning
confidence: 99%